1998
DOI: 10.1113/expphysiol.1998.sp004098
|View full text |Cite
|
Sign up to set email alerts
|

Effects of short chain fatty acids and carbon dioxide on magnesium transport across sheep rumen epithelium

Abstract: SUMMARYShort chain fatty acids (SCFAs)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
31
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 23 publications
3
31
0
Order By: Relevance
“…Part of the Mg 2ϩ influx is K ϩ sensitive and may represent electrodiffusive Mg 2ϩ uptake by an ion channel (35). The greater part (62%) is, however, K ϩ insensitive, and previous experiments carried out with isolated rumen epithelium and isolated ruminal epithelial cells (REC) in our laboratory have established that ruminal fermentation products [short-chain fatty acids (SCFA), CO 2 ] stimulate transepithelial Mg 2ϩ absorption (23) and Mg 2ϩ influx into REC (37). Initially, it was assumed that the stimulation of Mg 2ϩ transport was via Mg 2ϩ /H ϩ exchange in the apical membrane (23), by means of the proton load resulting from the absorption of SCFA in their protonized form and the intracellular hydration of CO 2 .…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Part of the Mg 2ϩ influx is K ϩ sensitive and may represent electrodiffusive Mg 2ϩ uptake by an ion channel (35). The greater part (62%) is, however, K ϩ insensitive, and previous experiments carried out with isolated rumen epithelium and isolated ruminal epithelial cells (REC) in our laboratory have established that ruminal fermentation products [short-chain fatty acids (SCFA), CO 2 ] stimulate transepithelial Mg 2ϩ absorption (23) and Mg 2ϩ influx into REC (37). Initially, it was assumed that the stimulation of Mg 2ϩ transport was via Mg 2ϩ /H ϩ exchange in the apical membrane (23), by means of the proton load resulting from the absorption of SCFA in their protonized form and the intracellular hydration of CO 2 .…”
mentioning
confidence: 96%
“…The greater part (62%) is, however, K ϩ insensitive, and previous experiments carried out with isolated rumen epithelium and isolated ruminal epithelial cells (REC) in our laboratory have established that ruminal fermentation products [short-chain fatty acids (SCFA), CO 2 ] stimulate transepithelial Mg 2ϩ absorption (23) and Mg 2ϩ influx into REC (37). Initially, it was assumed that the stimulation of Mg 2ϩ transport was via Mg 2ϩ /H ϩ exchange in the apical membrane (23), by means of the proton load resulting from the absorption of SCFA in their protonized form and the intracellular hydration of CO 2 . More direct investigations with isolated REC have provided evidence for a symport of Mg 2ϩ with anions and confirmed that SCFA and CO 2 activate H ϩ efflux by the Na ϩ /H ϩ exchanger (37).…”
mentioning
confidence: 99%
“…This variable interaction between K 1 intake and Mg 21 absorption has been quantified, permitting the prediction of Mg absorption (Weiss, 2004). The K 1 -insensitive Mg 21 absorption in the presence of high ruminal potassium is due to a second, electroneutral mechanism of Mg 21 absorption (Leonhard-Marek and Martens, 1996;Leonhard-Marek et al, 1998b Leonhard-Marek et al, 1998a, Leonhard-Marek, 1999Schweigel and Martens, 2003 (Schweigel and Martens, 2003;Etschmann et al, 2006).…”
Section: Absorption Of Magnesiummentioning
confidence: 99%
“…Three forms of Na ϩ -independent cation transport have been described: a Ca 2ϩ /Mg 2ϩ antiport in liver cells of the rat (Cefaratti et al 1998), where it appears to be restricted to the apical membrane of the cells; a Mg 2ϩ /choline exchange in rat erythrocytes (Ebel et al 2002); and a H ϩ -driven Mg 2ϩ extrusion in form of a 1 Mg 2ϩ /2 H ϩ antiport in epithelial cells from the colon and cecum of the rat (Scharrer and Lutz 1990) and possibly in the rumen of sheep (Leonhard-Marek et al 1998;see, however, Schweigel et al 2000).…”
Section: Introductionmentioning
confidence: 99%